2014
DOI: 10.1080/02103702.2014.881657
|View full text |Cite
|
Sign up to set email alerts
|

TuinLEC, an intelligent tutoring system to improve reading literacy skills / TuinLEC, un tutor inteligente para mejorar la competencia lectora

Abstract: This study describes an intelligent tutoring system to improve reading literacy skills called TuinLEC and it presents the results of its application to a group of sixth grade students. TuinLEC adopts the reading literacy theoretical framework of PISA (Program for International Students Assessment, OECD, 2009). TuinLEC includes eight lessons distributed in two phases, one for modeling and guided practice, and the second for independent practice. TuinLEC interacts with every student and it provides help and feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 27 publications
(76 reference statements)
1
6
0
1
Order By: Relevance
“…Although similar findings have been found in recent computerized intervention studies on taskoriented strategies in primary school students (Serrano, Vidal-Abarca & Ferrer, 2018;Vidal_Abarca, Gilabert, Ferrer, et al, 2014), this effect would require further systematic investigation in different learning contexts and different learners' populations.…”
Section: Discussionsupporting
confidence: 77%
“…Although similar findings have been found in recent computerized intervention studies on taskoriented strategies in primary school students (Serrano, Vidal-Abarca & Ferrer, 2018;Vidal_Abarca, Gilabert, Ferrer, et al, 2014), this effect would require further systematic investigation in different learning contexts and different learners' populations.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, two exclusion criteria were determined. Self-identified PISA articles refer to research that uses part of the study's material for a small independent sample (e.g., Vidal-Abarca, et al, 2014). Such articles, as well as commentaries on previous articles published in an academic journal, were excluded from the database.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…A study by Vidal-Abarca et al (2014) showed the efficacy of an intervention with TuinLEC (the previous version of TuinLECweb) to improve task-oriented reading performance in sixth-grade students.…”
Section: Tuinlecweb: An Itsmentioning
confidence: 99%
“…A study byVidal-Abarca et al (2014) showed the efficacy of an intervention with TuinLEC (the previous version of TuinLECweb) to improve task-oriented reading performance in sixth-grade students.However, important issues remain in need of further investigation, including (a) how students with different comprehension skills respond to TuinLECweb, not only in terms of performance but also in terms ofmonitoring accuracy and (b) the efficacy of this computer-based intervention compared with traditional classroom instruction. The first question is especially relevant because individuals with different comprehension levels differ in their use of task-oriented reading strategies (Cataldo & Oakhill, 2000; Maki et al, 2005; Vidal-Abarca et al, 2010) and…”
mentioning
confidence: 99%